Гидрогелевые нанореакторы медицинского назначения - Самченко, Ю.М.; Пасмурцева, Н.А.; Ульберг, З.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
Methods of the synthesis of hydrogelic nanoreactors to obtain nanosize particles of silver, magnetite, and hydroxyapatite have been developed. New composite materials can be used in medicine as antiburn dressings and magnetically responsive dosage forms and for the prosthetics of bone defects.